2021
DOI: 10.1161/jaha.120.016696
|View full text |Cite
|
Sign up to set email alerts
|

Novel Receptor for Advanced Glycation End Products‐Blocking Antibody to Treat Diabetic Peripheral Artery Disease

Abstract: Background Expression of receptor for advanced glycation end products (RAGE) plays an important role in diabetic peripheral artery disease. We proposed to show that treatment with an antibody blocking RAGE would improve hind limb perfusion and muscle viability in diabetic pig with femoral artery (FA) ligation. Methods and Results Purpose‐bred diabetic Yucatan minipigs with average fasting blood sugar of 357 mg/dL on insulin to maintain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…We treated diabetic mice with the murine anti‐RAGE Ab, and found that in mice treated with antibody, angiogenesis was enhanced compared with mice treated with vehicle. We extended this research to porcine model of diabetes with endovascular occlusion of the anterior femoral artery to show similar results of systemic administration of anti‐RAGE Ab to improve angiogenesis to the ischemic muscle in the limb occluded 30 . Other investigators demonstrated that soluble RAGE given as a decoy to diabetic db/db mice with full thickness dorsal wounds, showed accelerated wound healing in treated compared with untreated mice 6…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…We treated diabetic mice with the murine anti‐RAGE Ab, and found that in mice treated with antibody, angiogenesis was enhanced compared with mice treated with vehicle. We extended this research to porcine model of diabetes with endovascular occlusion of the anterior femoral artery to show similar results of systemic administration of anti‐RAGE Ab to improve angiogenesis to the ischemic muscle in the limb occluded 30 . Other investigators demonstrated that soluble RAGE given as a decoy to diabetic db/db mice with full thickness dorsal wounds, showed accelerated wound healing in treated compared with untreated mice 6…”
Section: Discussionmentioning
confidence: 76%
“…We extended this research to porcine model of diabetes with endovascular occlusion of the anterior femoral artery to show similar results of systemic administration of anti-RAGE Ab to improve angiogenesis to the ischemic muscle in the limb occluded. 30 Other investigators demonstrated that soluble RAGE given as a decoy to diabetic db/db mice with full thickness dorsal wounds, showed accelerated wound healing in treated compared with untreated mice. 6 Local approaches to treat diabetic wounds have included sustained topical administration of drugs in patches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the precise consequences of treatment with AGE-disrupting drugs remain a matter of debate, and there is a need for additional strategies to minimize matrix protein glycosylation. Encouragingly, an anti-RAGE monoclonal antibody that binds a peptide sequence in the RAGE extracellular structural domain prevented receptor-ligand binding and significantly improved hindlimb perfusion in ischaemic limbs, with greater reconstruction of collateral circulation in occluded arteries [ 132 ]. Recombinant proteins containing ELP fused to the RAGE domain or to stromal cell-derived factor 1 can inhibit AGE-RAGE signal transduction and promote cell proliferation and angiogenesis [ 133 ].…”
Section: Therapeutic Strategies For Promoting Angiogenesis By Targeti...mentioning
confidence: 99%
“…It inhibited HMGB1-induced IL-6 secretion from human peripheral bone marrow cells. The peptide sequences of this antibody are the same as for the antibody referred to as CR-3 in our recent publications [11,12].…”
Section: Antibodiesmentioning
confidence: 99%